Freak show [videorecording (DVD)] - Styler, Trudie; Lawther, Alex, 1995-; Breslin, Abigail, 1996-; Robb, AnnaSophia, 1993-; St. James, James; Midler, Bette (Shout! Factory, 2018)
Billy Bloom is one-of-a-kind: a fabulous, glitter-bedecked, gender-bending teenager whose razor-sharp wit is matched only his by his outrageous, anything-goes fashion sense. When his glamorous mother is forced to send him to live with his straight-laced father, Billy finds himself a diva-out-of-water at his new ultra-conservative high school. Undaunted by the bullies who don't understand him, the fearless Billy sets out to make a big statement in his own inimitable way.